Quantity Surveying Profession and Its Prospects in Nigeria - Uwadia E.F; Usman D.D.M; Amiebenomo M.I; Sumanu S.O, (Indian Journal of Management and Language (IJML), 2024)
The study assessed the prospects of the Quantity Surveying profession in Nigeria. The study identified and evaluated the level of performance of the identified functions performed by the quantity surveyors in the Nigerian Construction industry. The study reveals that there is a high level of performance of the basic functions of the quantity surveyors which include feasibility and viability studies, contract documentation, life cycle costing, preliminary cost advice, etc. The study also examined the factors militating against the effective performance of the quantity surveyor’s functions in the Nigerian Construction industry. The study identified and presented some possible factors militating against the performance of Quantity Surveying functions and some anticipated measures to enhance the quantity Surveying profession for evaluation by the respondents using structured questionnaires. The data collected were analyzed with SPSS version 23 using frequencies and mean item scores. The study revealed some major factors militating against the effective performance of the quantity surveying profession in the Nigerian Construction industry like widespread corruption in Nigeria with a mean score of 4.53, obsolete curriculum and inadequacy in modern equipment with a mean score of 4.41, professional rivalry from kindred profession with a mean score of 4.35, level of adoption of UT with mean a score of 4.32, and inadequacies in academic and professional training with a mean score of 4.18 among others. The study equally revealed some important measures requiring implementation to enhance the quantity of Surveying profession in Nigeria like a clear delineation in professional functions in the construction industry to curb professional rivalry with a mean score of 4.35, reviewing the curriculum of Tertiary Institutions with a mean score of 4.24, improving professional skills through continuing professional development with a mean score of 4.15, improving technological applications in the execution of Quantity Surveying functions with a mean score of 3.91 and professional certification in specialized areas with a mean score of 3.85.